Early Childhood Education an Care in Nigeria: Pedagogical Philosophy and Related Missing Links - Olalekan, Olatunji Michael (Indonesian Journal of Early Childhood Education Studies, 2018)
This paper reiterates the importance of Early Childhood Education and Care and gives a graphic account of Early Childhood Education in Nigeria. It also highlights England Denmark, Germany, France, Japan, New Zealand, Argentina, Cuba, Brazil, Costa Rica, Panama, Finland and Hong Kong as some of the nations that have made remarkable progress in Early Childhood Education and their specific positions on pedagogical approaches and their underlying pedagogical philosophies. Against this backdrop, a review of the state of Early Childhood Education in Nigeria is made with a focus on pedagogical approaches, their underlying pedagogical philosophies and related issue in this level of education. Proffered suggestion include relevant authorities ensuring that the national Curriculum is readily available to all stakeholders and that it contains sufficient direction an instructions for teachers so that they can teach and make maximum impact. The paper is theoretical, based on literature review. Key words: Early Childhood, Preprimary, Pedagogy, Neurology, National policy.